International Monetary Fund Annual Report 1980. (Annual Report of the Executive Board; Annual Report of the Executive Board, 1980)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1980. The report highlights that during the period from the beginning of 1979 to the middle of 1980, the world economic situation was marked by three disturbing features. Rates of inflation in most countries remained high and, indeed, accelerated. Growth of real output in the industrial countries began to slow down markedly, threatening to halt the expansion of world trade. Large surpluses and deficits reemerged in the external balances on current account for major groups of countries.